Model Madrasah Sains Integratif: Menakar Konsep dan Strategi Pembelajaran Berbasis Relasi Sains dan Agama - Anggun Zuhaida; Nur Hasanah; Wulan Izzatul Himmah (State Institute of Islamic Studies (IAIN) Salatiga, 2018)
AbstractRelations between science and religion are issues that have been developing for a long time, especially in Indonesia. Science as a pillar of human civilization cannot be separated from the attention of religions in the world. In Indonesia, efforts to establish the color of religion in its main education about scientific integration have been a concern in several Islamic universities. The purpose of this study was to find out the concepts and strategies of science and religion relations in learning in madrasas. This research method uses descriptive methods. The researcher measured the relation between science and religion by adapting to the approach developed by Ian G. Barbour which was divided into four: conflict; independence; dialog; and integration. The researcher found that the MTsN Kota Salatiga in the concept component was at the level of integration, but the strategy component was still at the level of dialogue. Whereas in the MTs NU Kota Salatiga it is known that the concept components and strategies are still at the level of dialogue.AbstrakRelasi ilmu dan agama adalah isu yang sudah cukup lama berkembang, utamanya di Indonesia. Ilmu sebagai pilar peradaban manusia, tidak dapat lepas dari perhatian agama-agama di dunia. Di Indonesia, upaya tentang adanya warna agama dalam pendidikan utamanya tentang integrasi keilmuan telah menjadi perhatian di beberapa perguruan tinggi islam. Tujuan dalam penelitian ini adalah, ingin mengetahui konsep dan strategi relasi sains dan agama dalam pembelajaran di madrasah. Metode penelitian ini menggunakan metode deskriptif. Peneliti menakar relasi sains dan agama tersebut dengan mengadaptasi dari pendekatan yang dikembangkan oleh Ian G. Barbour yang terbagi atas empat: konflik; independensi; dialog; dan integrasi. Peneliti menemukan bahwa pada MTsN Kota Salatiga dalam komponen konsep sudah pada tataran integrasi, namun pada komponen strategi masih pada tataran dialog. Sedangkan pada MTs NU Kota Salatiga diketahui bahwa pada komponen konsep, dan strategi masih pada tataran dialog.